New records of water beetles from families Helophoridae, Hydrophilidae and Heteroceridae (Coleoptera) from Uzbekistan - A.A. Prokin; A.S. Sazhnev; Ya.N. Kovalenko (Кавказский энтомологический бюллетень, 2016)
Ten species of water beetles are recorded for the first time from Uzbekistan: Helophoridae (Helophorus lapponicus C.G. Thomson, 1854, H. syriacus Küwert, 1885), Hydrophilidae (Berosus fulvus Küwert, 1888, B. bispina Reiche et Saulcy, 1856, Paracymus aeneus (Germar, 1824), Enochrus melanocephalus (Olivier, 1792), E.  fuscipennis C.G. Thomson, 1844, Cercyon quisquilius (Linnaeus, 1761)) and Heteroceridae (Heterocerus fusculus Kiesenwetter, 1843, H. obsoletus Curtis, 1828). The presence of Augyles turanicus (Reitter, 1887) in Uzbekistan is confirmed.